Nested PCR methods for detection Toxoplasma gondii B1 gene in Cerebrospinal Fluid of HIV patients - Ryan Halleyantoro; Yunilda Andriyani; Ika Puspa Sari; Agnes Kurniawan (Faculty of Medicine, Diponegoro University, 2019)
Background: Toxoplasmosis is a disease caused by infection of Toxoplasma gondii, Which may cause a life-threatening condition in immunocompromised patients, for example, Toxoplasma encephalitis (TE). It is challenging to diagnose Toxoplasma as a cause of central nervous system (CNS) infection in HIV patient, so we need an alternative method, which is a PCR detection of Toxoplasma gondii B1 gene.Objective: This research aimed to find association between PCR methods for Toxoplasma gondii B1 gene and anti-Toxoplasma IgG from cerebral spinal fluid patient HIV AIDS.Methods: A cross-sectional study was conducted to Cerebrospinal fluid (CSF) samples of HIV patients with neurological symptoms to determine Toxoplasma gondii infection using nested PCR methods for the B1 gene and detection of anti-Toxoplasma IgG.Results: 88 CSF samples from HIV patients tested using nested PCR showed 23 samples (26,1%) were positive. Serologic test for IgG Toxoplasma showed 34 samples were positive (28,6%). There was a significant correlation (p=0.000(<0.05) between PCR result and a serologic test for IgG Toxoplasma.Conclusion: Nested PCR methods to detect B1 gene increased the accuracy of diagnosis for toxoplasma encephalitis.